Service Quality and Operational Performance Management in BPJS Outpatient Registration During COVID-19 - Aldirafi Gani; Dwi Novitasari; Ervrensi Cinta Laura; W. Dian Dwi Maghriza; Farida Yuliaty; Vip Paramarta; Kosasih (Penerbit Goodwood, 2026)
Purpose: This study analyzes Social Security Administering Agency (Badan Penyelenggara Jaminan Sosial/BPJS) outpatient registration waiting time and integrates it with a SERVQUAL-based model to assess service quality and patient satisfaction during the COVID-19 pandemic.Research Methodology: This study used an integrative quantitative design that combined objective time-and-motion observations and a SERVQUAL questionnaire with a five-point Likert scale. The Service Quality (SERVQUAL) variables consisted of Tangibles (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), Empathy (X5), and Patient Satisfaction (Y).Results: The observation data showed an average total waiting time of 72.86 minutes, exceeding the ?60-minute national outpatient standard. Medical-record distribution averaged 18.80 minutes, while consultation waiting time averaged 44.31 minutes. The SERVQUAL analysis linked these delays to Reliability, Responsiveness, and Assurance as the most relevant dimensions in explaining patient satisfaction, with the regression model explaining 67.6% of the variance (R Square = 0.676).Conclusions: Waiting time can serve as an operational indicator for interpreting service quality using SERVQUAL. Reliability, Responsiveness, and Assurance are central dimensions for improving outpatient BPJS registration services.Limitations: The study was conducted in one hospital and one observation period during the COVID-19 pandemic.Contributions: This study offers a managerial framework linking waiting-time measurement, SERVQUAL dimensions, patient satisfaction, and operational improvement in hospital services